2018
DOI: 10.1111/mec.14474
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture shapes the trophic niche of a bat preying on multiple pest arthropods across Europe: Evidence from DNA metabarcoding

Abstract: The interaction between agricultural production and wildlife can shape, and even condition, the functioning of both systems. In this study, we i) explored the degree to which a widespread European bat, namely the common bent-wing bat Miniopterus schreibersii, consumes crop-damaging insects at a continental scale, and ii) tested whether its dietary niche is shaped by the extension and type of agricultural fields. We employed a dual-primer DNA metabarcoding approach to characterize arthropod 16S and COI DNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 56 publications
5
92
0
3
Order By: Relevance
“…This suggests that the diets of our study species could be determined by the abundance and availability of insect prey instead of any particular predator‐specific characteristic. In fact, it has previously been reported that bat diet responds to local insect population fluctuations (Aizpurua et al, ; Clare, Barber, Sweeney, Hebert, & Fenton, ; Sedlock, Krüger, & Clare, ; Vesterinen et al, ). Razgour et al () reported temporal shifts in the proportional frequencies of Lepidoptera and Diptera prey of P. auritus .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the diets of our study species could be determined by the abundance and availability of insect prey instead of any particular predator‐specific characteristic. In fact, it has previously been reported that bat diet responds to local insect population fluctuations (Aizpurua et al, ; Clare, Barber, Sweeney, Hebert, & Fenton, ; Sedlock, Krüger, & Clare, ; Vesterinen et al, ). Razgour et al () reported temporal shifts in the proportional frequencies of Lepidoptera and Diptera prey of P. auritus .…”
Section: Discussionmentioning
confidence: 99%
“…Following Aizpurua et al. (), Alberdi, Aizpurua, Gilbert, and Bohmann () and Kaunisto et al. (), we refrained from measuring the DNA concentration of individual libraries and instead pooled 2.5 μl of each indexed sample per sequencing run (i.e., each pool consisted of samples amplified with either COI or ITS+16S primers), then cleaned pools using dual SPRI purification to remove any possible artefacts or nontarget size amplicons (Wirta et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Geographic and temporal variation in trophic interactions is very common (e.g., Arrizabalaga‐Escudero et al, ; Clare, Barber, Sweeney, Hebert, & Fenton, ), thus studies that aim to generalize their results to be representative to a larger organismal group or explain global ecological processes need to account for such variation to avoid biased results. For example, when characterizing the dietary niche of a species, it is important to collect samples over a large geographic range, so as to avoid biases driven by local peculiarities (Aizpurua et al, ). In contrast, should a study wish to explore a predator's role in suppressing a prey species of particular local importance (e.g., pests of commercial crops), more localized studies may be required (e.g., Crisol‐Martínez, Moreno‐Moyano, Wormington, Brown, & Stanley, ).…”
Section: Designing a Dna Sequencing‐based Diet Studymentioning
confidence: 99%